Dynamic stability in unilateral transtibial prosthesis users - Kendell, Cynthia (University of Ottawa (Canada), 2009)
This study evaluated a multi-factorial, portable method of assessing dynamic-stability for unilateral transtibial prosthesis users. Twenty unilateral transtibial prosthesis users completed walking trials over various conditions (level and uneven ground, stairs, and a ramp). Plantar pressure data were collected using the F-Scan Mobile system. Six dynamic-stability parameters (relating to center of pressure motion, foot perturbations, and gait timing) were extracted from this data and dynamic-stability index values were calculated. Results showed that the parameters and index values differed between the intact and prosthetic limbs, between walking conditions, and between prosthesis users able-bodied subjects. Parameter and index values correlated poorly with stability criteria measures (Community Balance and Mobility Scale, Berg Balance Scale, Prosthetics Evaluation Questionnaire). Parameter and index calculations should be optimized for unilateral transtibial prosthesis users. Improved validation of the parameters and index is recommended, using an established, quantitative, dynamic-stability assessment method.
Keywords: Health Sciences, Recreation.